Characterization of wound-induced electrical signals and reactive oxygen species in chickpea (Cicer arietinum) - Deshpande, Shweta; Pawar, Shivani; Kumari, Archana (Plant Signaling & Behavior, 2025)
Mechanical damage to plants triggers both localized and systemic responses that activate plant defense mechanisms. Early signaling events include calcium (Ca2+) flux, reactive oxygen species (ROS), and electrical alterations. These signals coordinate downstream defense pathways, enabling plant acclimation to biotic stress. Electrical signaling following wounding/herbivory has been extensively studied in Arabidopsis; however, its dynamics in crop plants such as chickpea (Cicer arietinum) are not well understood. The pattern of the SWP in chickpea was similar to that in Arabidopsis but with a longer repolarization phase and was detectable only within the leaflets. The signals generated by damaging the leaflet were more pronounced, propagated bidirectionally and varied between herbivore-susceptible and tolerant chickpea varieties. The SWP duration is correlated with increased expression of AOS and OPR3 transcripts, which are markers of the stress hormone JA. Additionally, ROS production in wounded chickpea leaflets is associated with increased expression of ROS-generating genes. The use of DPI, an inhibitor of NADPH oxidase, which is responsible for ROS production, inhibited SWP, suggesting the crucial role of ROS in wound-induced SWP. This study provides insight into the interplay between wound-induced electrical signaling and ROS production in chickpea and proposes the measurement of electrical signals as a rapid, noninvasive approach for screening crop cultivars for pest susceptibility and tolerance.
Keywords: Chickpea; Electrical signal; Plant defense; ROS; wound